2016
DOI: 10.1371/journal.pone.0155221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gear Restriction on the Abundance of Juvenile Fishes along Sandy Beaches in Hawai‘i

Abstract: In 2007, due to growing concerns of declines in nearshore fisheries in Hawai‘i, a ban on gillnets was implemented in designated areas around the island of O‘ahu in the main Hawaiian Islands. Utilizing a 17 year time-series of juvenile fish abundance beginning prior to the implementation of the gillnet ban, we examined the effects of the ban on the abundance of juveniles of soft-bottom associated fish species. Using a Before-After-Control-Impact (BACI) sampling design, we compared the abundance of targeted fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Even though the interaction term of protection and time was not significant, dissimilarities between periods were found both in the PPA and FPA, suggesting that assemblages are possibly being influenced by management measures. Optimal design should have included sampling prior to the management plan implementation ( Claudet & Guidetti, 2010 ; Donovan et al, 2016 ). First samples were collected with some regulations already in place and protection effect may have been larger than what our data suggests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the interaction term of protection and time was not significant, dissimilarities between periods were found both in the PPA and FPA, suggesting that assemblages are possibly being influenced by management measures. Optimal design should have included sampling prior to the management plan implementation ( Claudet & Guidetti, 2010 ; Donovan et al, 2016 ). First samples were collected with some regulations already in place and protection effect may have been larger than what our data suggests.…”
Section: Discussionmentioning
confidence: 99%
“… Pipitone et al (2000) also described increases in the abundance and biomass of some soft-bottom fishes (e.g., Mullus barbatus and Lepidotrigla cavillone ) after a trawling ban in a Mediterranean MPA. More recently, Donovan et al (2016) reported the effects of a gillnet ban in a sandy coastal area of Hawai‘i, and highlighted the variability of response according to species group, as only bonefishes ( Albula spp.) exhibited a positive trend.…”
Section: Introductionmentioning
confidence: 99%
“…Gill nets are regulated in some areas in Hawai‘i (e.g., Kailua, a large portion of the south shore of O‘ahu, number of locations in West Hawai‘i, and the entire island of Maui) ( Division of Aquatic Resources, 2017 ). Justification for these bans was the indiscriminate catch, including juvenile fishes, and a high bycatch of threatened and endangered species (e.g., sea turtles, marine mammals) ( Smith, 1993 ; Blaber et al, 2000 ; Donovan et al, 2016 ). Certain methods of spear fishing such as nighttime and/or on scuba are highly efficient, particularly for parrotfishes, which sleep on the reef at night and are easily harvested at that time ( Richmond et al, 2002 ; Sabetian & Foale, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resources, 2017). Justification for these bans was the indiscriminate catch, including juvenile fishes, and a high bycatch of threatened and endangered species (e.g., sea turtles, marine mammals) Blaber et al, 2000;Donovan et al, 2016). Certain methods of spear fishing such as nighttime and/or on scuba are highly efficient, particularly for parrotfishes, which sleep on the reef at night and are easily harvested at that time (Richmond et al, 2002;Sabetian & Foale, 2006).…”
Section: Output Controlsmentioning
confidence: 99%